2021
DOI: 10.3390/ijerph181910462
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Survey of Mental Health Social Work in Europe

Abstract: This article reports on an exploratory study comparing mental health social work (MHSW) in Europe. There has been very limited previous research comparing approaches to MHSW in Europe and so the aim of the study was to develop a better understanding of the similarities and differences between and, where relevant, within countries (referred to as jurisdictions). An online survey was distributed mainly through existing European networks and social media to seek information on the role, nature, extent and context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…This reflects a wider context for social work as an under-researched subject area and the need to build research capacity to find out more about what social workers actually do on the ground and the influences that shape their practice [47]. How the mental health social work role is defined and understood in different jurisdictions is particularly under-researched [48]. With this in mind, the authors are cognisant that mental health social workers, and social workers more broadly, might be developing practice approaches that would fit with the CRPD's principles but are hidden from the literature.…”
Section: The Evidence Gapmentioning
confidence: 99%
“…This reflects a wider context for social work as an under-researched subject area and the need to build research capacity to find out more about what social workers actually do on the ground and the influences that shape their practice [47]. How the mental health social work role is defined and understood in different jurisdictions is particularly under-researched [48]. With this in mind, the authors are cognisant that mental health social workers, and social workers more broadly, might be developing practice approaches that would fit with the CRPD's principles but are hidden from the literature.…”
Section: The Evidence Gapmentioning
confidence: 99%
“…Stone et al's [52] Europe-wide study valuably illustrates that statutory duties are not a universal aspect of mental health social work, providing a contextualizing balance to the dominance of formal legal imperatives in the British studies. Nonetheless, even in national contexts that do not have specific statutory roles that can be fulfiled by social workers, Stone et al [52] found that practice is influenced by broader statutory and rights-based contexts, such as in foregrounding human rights in mental health services.…”
Section: Legal Rolesmentioning
confidence: 99%
“…In a British context, both AMHP and non-AMHP social workers identified organizational dysfunctions, such as a lack of preventative services and late referrals for support, as limiting the fulfilment of social work skills and values in practice [35,41,44,[52][53][54]. There was evidence in the English context of the integration of social workers into NHS mental health teams, often through secondment from Local Authorities, as enabling social work leadership in promoting social considerations of mental health needs [33].…”
Section: Organizational Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis on health and social care systems has proven to be a useful tool for assessment and gaining new insights into administrative decision-making [ 15 , 16 , 17 ]. In this branch of study, descriptive methods can help to identify population sets (i.e., elderly or disabled population) and determine which social characteristics influence their need for public services such as home-based social care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%